Skill Acquisition Methods Fostering Physical Literacy in Early-Physical Education (SAMPLE-PE): Rationale and Study Protocol for a Cluster Randomized Controlled Trial in 5–6-Year-Old Children From Deprived Areas of North West England - Rudd, James R.; Crotti, Matteo; Fitton-Davies, Katie; O’Callaghan, Laura; Bardid, Farid; Utesch, Till; Roberts, Simon; Boddy, Lynne M.; Cronin, Colum J.; Knowles, Zoe; Foulkes, Jonathan; Watson, Paula M.; et al. (Frontiers in Psychology, 2020)
BACKGROUND: There is a need for interdisciplinary research to better understand how pedagogical approaches in primary physical education (PE) can support the linked development of physical, cognitive and affective aspects of physical literacy and physical activity behaviours in young children. The Skill Acquisition Methods fostering Physical Literacy in Early-Physical Education (SAMPLE-PE) study aims to examine the efficacy of two different pedagogies for PE, underpinned by theories of motor learning, to foster physical literacy, especially for children living in disadvantaged areas. METHODS: SAMPLE-PE will be evaluated through a cluster-randomised controlled trial targeting 5-6 year old children from schools located in areas of high deprivation in Merseyside, North-West England. Schools will be randomly allocated to one of three conditions: Linear Pedagogy, Nonlinear Pedagogy or Control. Nonlinear and Linear Pedagogy intervention primary schools will receive a PE curriculum delivered by trained coaches over 15 weeks, while control schools will follow their usual practice. Data will be collected at baseline (T0), immediately post-intervention (T1) and six months after the intervention has finished (T2). Children’s movement competence is the primary outcome in this trial. Secondary outcomes include physical activity, perceived competence, motivation, executive functions, and self-regulation. An extensive process evaluation will also examine implementation factors such as intervention context, reach, dose, fidelity and acceptability. DISCUSSION: The SAMPLE-PE project will enable better understanding surrounding how to operationalise physical literacy through enrichment of PE practices in early PE. The study will provide robust scientific evidence regarding the efficacy of underpinning PE pedagogy with theories of motor learning to promote the development of physical literacy.